The Impact of Promotional Tools on Consumer Buying Behavior: A Study from Pakistan - Rizwan, Muhammad; Javed, Muhammad Arif; Khan, Muhammad Tayyab; Aslam, Muhammad Tariq; Anwar, Kashafa; Noor, Sanna; Kanwal, Wajiha (Asian Journal of Empirical Research, 2013)
The main objective of this research was to investigate the influence of sales promotion and physical surroundings that is situational factor on consumer buying behavior. The research found that there was no significant relationship between free samples, coupons and buying behavior. On the other hand price discount, buy-one-get-one-free, physical surrounding has a significant relationship with buying behavior. The results of regression analysis show that price discount, buy-one-get-one-free and physical surroundings explained 45.7% variance in buying behavior of the respondents. The results of this research would assist marketers to understand the best kind of promotion tool that significantly affect buying behavior of the consumers. The marketers can develop their business plan more effectively through the result of this study and these plans help businessmen and marketers to gain competitive advantage over their competitors and enable the businesses to earn maximum profit.